2021
DOI: 10.3390/su132112273
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of the Relationships between Nostalgia, Involvement, and Behavioral Intention in Diaspora Tourism

Abstract: Diaspora tourism has become a significant market niche under globalization, but diaspora tourism to China has been less studied. This paper explores the relationships between nostalgia, involvement, and behavioral intention in diaspora tourism of the Chinese diaspora. By investigating 303 overseas Chinese, we use quantitative methodologies to measure the nostalgia of the Chinese diaspora and identify three segments of Chinese diasporic tourists based on their nostalgia: extremely nostalgic, nostalgic, and mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The measurement of Effectiveness of Heritage Building Revitalization referred to the scale of Chang et al (2020) , which consists of 3 dimensions: Appearances and Components, Building Technologies and Planning and Contributions. The measurement of Local Cultural Identity is based on the scale of Zeng and Xu (2021) , and the measurement of Knowledge Transfer is based on the scale of Liu (2018) . Cultural Activities Engagement refers to the scale of Peng et al (2023) .…”
Section: Methodsmentioning
confidence: 99%
“…The measurement of Effectiveness of Heritage Building Revitalization referred to the scale of Chang et al (2020) , which consists of 3 dimensions: Appearances and Components, Building Technologies and Planning and Contributions. The measurement of Local Cultural Identity is based on the scale of Zeng and Xu (2021) , and the measurement of Knowledge Transfer is based on the scale of Liu (2018) . Cultural Activities Engagement refers to the scale of Peng et al (2023) .…”
Section: Methodsmentioning
confidence: 99%
“…The limitations of such an argument centre on its emphasis on the institutionalised formal arrangements, suggesting assimilation [29] and ignoring latent and informal learning and internalisation as well as hybridity, which can equally foster sustainability (which is increasingly and inherently discussed in relation to global groups). This argument also negates the weight of psychological factors, such as nostalgia [30] and homesickness [11], in the speed of internalisation and hybridisation of local norms.…”
Section: Rethinking Cultural Capitalmentioning
confidence: 99%
“…The concept of diaspora tourism is closely related to the concept of stem tourism or heritage tourism, as it involves visiting places of personal or ancestral significance (Huang and Chen, 2020). Research has identified various motivations for diaspora tourists, including nostalgia, cultural exploration, family reunions, religious and spiritual connections, and the desire to learn about one's ancestral homeland (Otoo et al, 2020;Zeng & Xu, 2021;Mohammed et al, 2021). Li and McKercher (2016) found that individuals who maintain a strong connection to their original identity and culture of origin are the most motivated to take diaspora trips.…”
Section: Literaturementioning
confidence: 99%
“…The concept of diaspora tourism is vital and is a way for individuals to maintain a relationship with their original homeland (Zeng & Xu, 2021). It allows individuals to experience a sense of belonging to their homeland on a social and emotional level (Uriely, 2010;Etemaddar et al, 2016).…”
Section: Literaturementioning
confidence: 99%